AN ANALYSIS OF FACTOR THAT INFLUENCE THE LEVEL OF KNOWLEDGE OF SMES ABOUT ACCOUNTING OF SMES (A CASE STUDI AT SMES IN SUBANG REGENCY) - Virly Ramdhani; Sri Mulyati; Trisandi Eka Putri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
The economy in Indonesia is dominated by small and medium enterprises (SMEs), so some opinion state that small and medium enterprises (SMEs) are able to increase nation’s economic system from both income and employment. Institute of Indonesia Chartered Accountants created a new Financial Accounting Standards (FAS) to facilitate SMEs in making financial reports that SAK EMKM (Micro Small and Medium Entities) made more simple than SAK ETAP. The research method undertaken by the author in this paper is quantitative descriptive method using multiple linear regression analysis tool, the survey was conducted to 100 respondents of SMEs in Subang district. The data used are ordinal and interval data. Statistical methods for testing the data author used the SPSS 22 program. By using multiple linear regression analysis obtained equation Y = 2,189 + 0,091X1 + 0,031X2 + 0,418X3 + 0,163X4 - 0,047X5 + 0,004X6 + e. From the research result, it is known that social environment and cultural environment and economic variables have significant effect to knowledge level of Accounting of SMEs, while education, information / mass media, experience, and age variables have no effect on knowledge level of Accounting of SMEs. These variables simultaneously affect the knowledge level of Accounting of SMEs.